Spatial attention modulates tactile change detection. - Van Hulle, L; Van Damme, S; Spence, C; Crombez, G; Gallace, A (2013)
People often fail to detect changes between successively presented tactile patterns, a phenomenon known as tactile change blindness. In this study, we investigated whether changes introduced to tactile patterns are detected better when a participant's attention is focused on the location where the change occurs. Across two experiments, participants (N = 55) were instructed to detect changes between two consecutively presented tactile patterns. In half of the trials, the stimulated body sites in the two patterns were identical. In the other half of the trials, one of the stimulated body locations differed between the two patterns. Endogenous (or voluntary) attention was manipulated by instructing participants which new bodily location was most likely to be stimulated. We found that changes at the attended location were detected more accurately than changes at bodily locations that were unattended. This finding demonstrates that attention can effectively modulate tactile change detection. We discuss the value of this experimental paradigm for investigating excessive attentional focus or hypervigilance to particular regions of the body in various clinical populations.